STUDI KASUS: HYDROTHERAPY PADA CEREBRAL PALSY ATHETOID CASE STUDY: HYDROTHERAPY IN CEREBRAL PALSY ATHETOID (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2021)
Background: Dyskinetic / athetoid cerebral palsy is caused by damage to the basal ganglia of the brain. The basal ganglia are responsible for sending messages to the body to help coordinate and control movement.Objective: To determine the implementation of physiotherapy in increasing muscle strength, maintaining spasticity, functional ability, and standing balance in cases of spastic quadriplegy athetoid cerebral palsy using the Halliwick method of hydrotherapy as a modality.Results: After 4 times therapy for spastic quadriplegy athetoid cerebral palsy, the results of the assessment on spasticity from T1 to T4 did n ot increase spasticity, muscle strength increased in the abductor hip from T2: 3 to T3: 4, flexor knee dextra T1: 3 to T4: 4, plantar flexor ankle dextra from T3: 3 to T3: 4. In gross motor skills increased from T1: 64.5% to T3: 65.8%, and from balance in standing static T1: 7 seconds, T2: 15 seconds, T3: 22 seconds, T4: 23 seconds, and balance in stepping is able to T1: 1 step to T2: 3. Improvement in GMFM motor functional abilities T1: 64.5% to 65.8% at T4, Increase in standing balance T1 : 7 seconds at T4 to : 23 Seconds, on the ability to step T1 : 1 step at T4 to : 2 steps.Conclusion: Halliwick's hydrotherapy method can improve muscle strength, maintain spasticity, improve standing and walking balance abilities and improve motor functional abilities in cases of athetoid spastic quadriplegy cerebral palsy.Keywords: Dyskinetic cerebral palsy, athetoid spastic quadriplegic cerebral palsy, Hydrotherapy